Survey of Northwest Kansas cow-calf producers - Simms, D.D.; Boyd, G.; Corah, L.R. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An in-depth survey of reproductive performance and management practice was conducted on 160 cow/calf operations in Northwest Kansas.
Keywords: Beef; Cow-calf; Reproductive performance; Management